The Relationship Between Serum Pentraxine 3 Levels and Hematological Markers in Patients With Rheumatoid Arthritis - Mustafa Serdar SAĞ,; Sinem SAĞ,; İbrahim TEKEOĞLU,; Ayhan KAMANLI,; Kemal NAS,; Halil HARMAN, (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate the association of pentraxin 3 (PTX3) with neutrophil/lymphocyte ratio (NLR) rather than the disease activity score 28 using C-reactive protein in rheumatoid arthritis (RA). Patients and methods: The study included 59 RA patients (11 males, 48 females; mean age 53.79±13.55 years; range 40 to 66 years) and 20 healthy controls (5 males, 15 females; mean age 50.41±6.11 years; range 43 to 56 years). Complete blood count tests were recorded and NLR and platelet/ lymphocyte ratio were calculated. PTX3 and interleukin-6 levels were examined in serum samples. Disease activity of RA patients was assessed by disease activity score 28. Results: Demographic characteristics were similar between the two groups, with no statistically significant difference in terms of sex, age, and body mass index (p>0.05). NLR, PTX3 and interleukin-6 levels were higher in patients with RA than the control group (p<0.05). While erythrocyte sedimentation rate had a positive correlation with mean platelet volume, we found no correlation between NLR and other parameters of disease activity, PTX3, and interleukin-6. Conclusion: We found no correlation between PTX3 and disease activity score 28 or NLR, although PTX3 levels were higher in RA patients than the controls. As a result, we were unable to establish a relationship between PTX3 and disease activity, directly or indirectly. To our knowledge, our study was the first to investigate the relationship between PTX3 and NLR.